Rumi and women : depiction of the complexity of the female psyche in the mathnawi - Sedighi, Banafsheh Hassas
This thesis explores why and how Rumi depicted women in the Mathnawi. This research covers mythologies and religious beliefs from Judaism to Christianity and Islam; philosophers from ancient Greece until today and shows that different cultural settings from the Middle East to China have always perceived women negatively. This finding is crucial because it serves as a general framework within which we find references to understanding Rumi's standpoint against women. The work identifies certain expressions in Rumi's works, which can be considered misogynistic. On the other hand, our findings also demonstrate that Sufism, with strong references to the Qur'an and the Hadith, constitutes the main basis for Rumi's perception of women. Rumi's consistent constructive relations with women around him confirm the finding that Sufism led Rumi to regard women positively. A deeper analysis reveals that when Rumi uses women in a negative context, he does not do so to insult them. He uses humour, symbols and vulgarity at times associated with women to convey his messages. The main conclusion drawn from this research is that considering his general philosophy of women and his daily encounters with them, Rumi's perception of women is positive and that he does not see them as less than men.